2015
DOI: 10.1111/socf.12166
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Veterans of the Wars in Iraq and Afghanistan in the U.S. Media

Abstract: To evaluate how the media frames veterans of the wars in Iraq and Afghanistan, this study systematically assesses the discourse on Iraq and Afghanistan veterans in the New York Times and Washington Post from 2003 to 2011. Our analysis of a stratified sample of 151 articles featuring veterans from either the wars in Iraq or Afghanistan finds that the media frames veterans as damaged by their service but deserving of government benefits and social assistance. When the media frames veterans as actively engaging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 29 publications
2
37
1
Order By: Relevance
“…Furthermore, existing studies (e.g., Kleykamp & Hipes, 2015) have focused on media portrayals of veterans as being damaged by their service and, therefore, deserving of generous benefits, but the veterans in this study displayed a different emphasis, describing the media as misrepresenting their wartime experiences with exaggeration and omissions. This theme of negative perceptions of the media supports prior qualitative research with OIF/OEF veterans (Brinn & Auerbach, 2015).…”
Section: Meanings Made and Barriers To Meaning-makingmentioning
confidence: 92%
“…Furthermore, existing studies (e.g., Kleykamp & Hipes, 2015) have focused on media portrayals of veterans as being damaged by their service and, therefore, deserving of generous benefits, but the veterans in this study displayed a different emphasis, describing the media as misrepresenting their wartime experiences with exaggeration and omissions. This theme of negative perceptions of the media supports prior qualitative research with OIF/OEF veterans (Brinn & Auerbach, 2015).…”
Section: Meanings Made and Barriers To Meaning-makingmentioning
confidence: 92%
“…Yet, such portrayals can also be personally and professionally hurtful. Notably, such portrayals are often at odds with the way in which many veterans see themselves and characterize their military experience (National Veterans Foundation, 2016;Parrott et al, 2018;Pew Research Center 2011), and have been shown to cause the general public to develop a very narrow understanding of veterans (MacLean & Kleykamp, 2014;Kleykamp & Hipes, 2015;Wilbur, 2016), and even diminish employment opportunities for veterans reentering the civilian workforce (Hunter, 2017).…”
Section: Coverage Of Military Service Members and Veteransmentioning
confidence: 99%
“…Combat veterans generally do not desire attention nor seek acclaim for their service. At the same time though, veterans can become extremely angry or irritated if their service is ignored, minimized, or not acknowledged (Kleykamp & Hipes, 2015). Further, many combat veterans will become extremely upset if the wars they fought in are criticized, viewing such criticisms as assaults on their service, sacrifice, and accomplishments.…”
Section: Modesty Paradoxmentioning
confidence: 99%